The Potential of Asking and Critical Thinking of Students in the Course of Development of Teaching Materials Through Problem-Based Learning Models - Hartono D. Mamu (Peneliti.net, 2023)
The purpose of this research is to describe the potential of students to ask questions and think critically in the subject of developing teaching materials using the problem-based learning model. Research using descriptive methods; data collection using observation sheets of asking activities, and tests of critical thinking skills in the form of essays. Data analysis was carried out descriptively. The results showed that the average percentage of student questions was dominated by the low-level thinking category (LOTS) by 80%; the question category of higher-order thinking (HOTS) by 20%. The percentage of student questions in the HOTS category is 69.2% lower than in the LOST category. In the aspect of critical thinking skills, the mean value of the interpretation indicator is 82.80; analysis 84.05; inference 79.6; evaluation 81.0; explanation 75.3; and indicators of self-regulation worth 70.5. Based on the results of the study, it can be concluded that the problem-based learning model can facilitate students to increase their potential to ask questions and think critically in learning the development of teaching materials.